Inovasi Pelayanan Sistem Informasi Manajemen Nikah pada Kantor Urusan Agama Kecamatan Johan Pahlawan Aceh Barat - Via Anisa; Dyah Lituhayu; Budi Puspo Priyadi; Teuku Afrizal (PERSPEKTIF, 2023)
This study identified innovative efforts for the Marriage Management Information System (SIMKAH) to improve marriage administration services at the Religious Affairs Office (KUA) in Johan Pahlawan District, West Aceh Regency. Knowing the Services of the Marriage Management Information System (SIMKAH) at the Religious Affairs Office (KUA) in Johan Pahlawan sub-district, West Aceh Regency. Public service innovations are ideas and modifications that can benefit the community directly. Public service innovation makes a public service system better, more effective and efficient. The research was conducted at the Office of Religious Affairs (KUA) in Johan Pahlawan District, West Aceh Regency. The research method uses a qualitative descriptive approach, while the data sources used are Primary Data and Secondary Data. The results of the study show that the Marriage Management Information System (SIMKAH) is an innovation in providing services to be effective and efficient. However, there are obstacles in implementing its services on asynchronous systems, surveys, networks and data. Instead, actions for improvements in improving these things need to be implemented. So that this innovation can be more beneficial to the service system and society